EVALUASI TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN METODE COBIT 5 DI STKIP TAMAN SISWA BIMA - Supriyaddin Supriyaddin; Wing Wahyu Winarno; M Rudiyanto Arief (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2017)
This research used to evaluate the governance Information Technology (IT) in application using COBIT 5 standard and recommend input to create IT management in the implementation of SIMAKOM STKIP Taman Siswa Bima for the better. The domains chosen in this study are domain of Evaluate, Direct and Monitor (EDM) 01 and Deliver, Service and Support (DSS) 05 of 37 domains in COBIT 5.The three primary data collection techniques used were the interviews, questionnaire and observation. the researcher used quantitative method by applying Rating Scale. The average value of the capability level on the EDM01 domain is at level 1 (Performed Process) where the current IT governance condition indicates that the at STKIP Taman Siswa Bima has implemented a process to achieve the objectives while the average capability level in the DSS 05 domain is at the level 2 (Managed Process) where the current condition of IT shows that the at STKIP Taman Siswa Bima has implemented a process of planning, monitoring and adjusting a process to achieve the direction.Target capability levels are expected to reach at level 2 of the EDM01 domain and level 3 on the DSS05 domain, then all processes specified in each process in each domain must be fulfilled and implemented.